Asuhan Kebidanan Komprehensif pada Ny. N di RSUD Labuang Baji Makassar - Fauziah. H, Putri; Syarief, Suchi Avnalurini; Husnah, Nurul (Window of Midwifery Journal, 2025)
Maternal mortality rate and infant mortality rate in Indonesia are one of the indicators to see the government's efforts to improve health success. Pregnancy, childbirth, postpartum, and newborns are conditions that occur physiologically but these conditions can also threaten the lives of mothers and babies and result in death for both mothers and babies. Midwives have an important role in providing comprehensive midwifery care, starting from antenatal, intranatal, newborns, postnatal to family planning. The purpose of this study is to be able to provide comprehensive midwifery care. This study uses data collection methods with Varney's 7-step midwifery care management and SOAP. The patient who was assessed was Mrs. N at Labuang Baji Hospital, Makassar in 2024 with a normal pregnancy, normal delivery without complications, the baby was born spontaneously with a birth weight of 3200 grams, birth length 49 cm, head circumference 34 cm, and chest circumference 32 cm, the postpartum period was normal and counseling was given regarding various types of contraception. From the results of the study, it can be concluded that during pregnancy, childbirth, newborns, postpartum to family planning in Mrs. N at Labuang Baji Hospital, Makassar in 2024, everything went normally without any complications.